Vertical Separation. - Bonanno, G; Vickers, J (1988)
A simple duopoly model is used to show the advantage to a manufacturer of selling his product through an independent retailer (vertical separation) rather than directly to consumers (vertical integration). Vertical separation is profitable insofar as it induces more friendly behavior from the rival manufacturer. The authors consider the case where franchise fees can be used to extract retailers' surplus. They show that vertical separation is in the collective, as well as individual, interest of manufacturers, and hence facilitates some collusion in the simple setting that they examine.